Offering a Method to Find the Most Proper Parking Space in the City Automobile Expediency Network by Genetic Algorithm - Marziyeh, A.; Farzaneh, S. (Наука та інновації, 2019)
Finding a free space for parking in rush hours and heavy traffic has been always a boring and time-consuming problem for drivers. Recently, VANET networks have found special attention among economists and university researchers. Due to day-by-day expansion of wireless communicative systems, many car manufacturers have been installing such communicative tools as OBU on their products. The RSU tools give drivers the possibility to have better and more convenient means of communication. They can trace the availability of parking spaces using these tools and be guided to there, while the automobiles can be equipped with anti-burglar systems to have a higher security. In this research, a comprehensive method using the genetic algorithm have been offered to find a place for parking in the automobile expediency network, which has considered many parameters such as parking space being located near or far, cost of parking space for drivers, the probability of parking space remaining available until the car arrives and reduced past defects as much as possible.